Modification of Diesel Hydraulic Locomotive ConsideringCrashworthiness Aspect - Hadi, Isra
Indonesian railway safety system needs improvement. During 2004-2010, the total ofaccidents are 175. In order to reduce the accident risks, 2 safety systems can be used, namely active and passive safety system. Active safety system (ATP) to avoid accidents has been implemented by KA General Directorate. Beside that, passive safety system such as crashworthiness technology is also necessary to reduce the consequences of the accidents. As an application of the passive safety systems, thisfinal project has been carried out to obtain a better design based on crashworthiness aspectsand comparison of the impact absorption between the existing and modified design. Modificationis limited only in the cowcatcher area. Impact absorption system used containsa collapsible structure and impact absorber module. Crashworthiness analysis is based on European standard BS EN 15227:2008, which is aimed at 3 targets, namely: (1) 4.6 MJ impact absorption on the front end of locomotive with maximum force 3.4 MN, (2) 4.5 MN maximum force on the first 5 ms, and (3) max. deceleration is 5g. From the result of impact analysis, it is concluded that existing locomotive has a low crashworthiness performance. After 2 modification, the crashworthiness parameter shows a better results. The impact absorption energy can reach 2.07 MJ, with the maximum force of 7.13 MN. The maximum force on the first 5ms is 5.71 MN and 3.14g for deceleration.Collapsible structure has5 pairs of plates, with 3 vertical pairs and 2 horizontal pairs. Plate thickness is 7mm, 60 mm for plate height, and 80 mm for each of partition length. Impact absorber module design, diameter 4 in., 2 mm thickness, with SS400 material. From both of two modification results, it was concluded that the application of crashworthiness givebetter results. However, with the design constraints, modification is not qualified based on standard criteria.